An economic perspective on the Irish monetary tithe: A trigger for Irish banditti and secret societies disturbances - Daniel John Shaw (The Journal of European Economic History (JEEH), 2021)
By the mid-18thcentury, the Irish tithe in kind was converted into amonetary tithe (known as the modus decimandi) that systematicallyproduced relatively high tithing rates upon a poor harvest andshifted the revenue risks borne by the clergy to tillage farmers. Butthis added risk burden - best exemplified by high tithing rates rel-ative to harvest revenues - only served to reinvigorate thegroundswell of protest and violence that accompanied the manyregional food riots provoked by a series of devastating harvestswhich, in turn, had created a subsistence crisis and the potentialthreat of famine. Taking the form of a secret society, these newestprotestors - the "banditti" - took direct aim at the tithe, interveningby setting much lower rates backed up by violence (mostly againsttithe agents). In 1823, Parliament responded to these disturbancesby revamping the tithe in favour of a "composition", making it com-pulsory only from 1832. However, the enactment of the mandatoryprovision triggered renewed protests and violence and the ensuingconflicts escalated into what became known as the Irish Tithe Warof 1831-1838. This paper examines the tithing rates of the modusdecimandiregime in terms of its share of annual crop revenuesunder different harvest scenarios and estimates the potential addedrevenue risks borne by tillage farmers under both monetary titheregimes. This investigation finds that the primary cause of these se-cret society tithe disturbances, like that of the Irish Tithe War, wasan increase in revenue risk that fell harshly upon small tillage farm-ers and for which there was insufficient compensation.
Keywords: 330